Implementation of Immigration Function for Protection of Indonesian Migrant Workers - Achmad Setiawan. S (Jurnal Ilmiah Kajian Keimigrasian, 2020)
Indonesia is one of the most populous countries in the world. It makes an imbalance between the availability of employment and the total population, thus causing some citizens choose to become migrant workers in order to support their families. Along with the increase in the flow of migrant workers, it is also equivalent to the emergence of various problems related to migrant workers. Therefore, the Government needs to take steps to protect Indonesian migrant workers. In this paper, the author discusses the role of the Directorate General of Immigration in the implementation of the chess function of immigration for Indonesian migrant workers, while among others the Prevention of Non-Procedural PMI, facilities for migrant workers in border areas, and also supervision for PMI abroad. The method used is Empirical Juridical, which links the legal basis in this case the regulation of laws relating to the facts that occur in the community.